Legal Analysis of the Procedure for Determining Contentious Heirs at the Banda Aceh Sharia Court - Rian Apriesta Ramsadefa; Ilyas Yunus; Zahratul Idami (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
The determination of contentious heirs at the Banda Aceh Syar'iyah Court is a legal procedure carried out when not all heirs are involved in submitting an application for determination of heirs. However, in practice, this application is still rarely submitted and is poorly understood procedurally. This study aims to analyze the Application Procedure for the Determination of Contentious Heirs applied at the Banda Aceh Syar'iyah Court and the obstacles and obstacles faced in the implementation of the Application Procedure for the Determination of Contentious Heirs at the Banda Aceh Syar'iyah Court. This research uses a type of empirical juridical research, which is research that examines law not only as a written norm but also as real behavior in judicial practice. Data were obtained from field research, interviews, and literature. Data analysis uses qualitative methods. The results of the study show that the contentious procedure includes the stages of summoning the respondent, mediation, reading of the application, answers, replicas, duplicates, proof, conclusions, and decisions by the panel of judges, as well as opening up opportunities for legal remedies such as appeals, cassation, and review. The submission of an application for the determination of heirs in a contentious manner is often constrained because the defendant refuses to participate or his whereabouts are unknown, thus hindering the court process and the fulfillment of inheritance rights.